Hipoteza Tłumienia Sorokina w Przypadku Drgań Aperiodycznych - Skarżyński, R. (Engineering Transactions, 1973)
This paper presents the method of generalization of the viscoelastic model of a Sorokin body and its application to cases of aperiodic vibrations of structures. The method is illustrated by examples.